The Impact of Auditory Perceptual Training on the Perception and Production of English Vowels by Cypriot Greek Children and Adults. Issue 4 (2nd October 2022) - Georgiou, Georgios P.
ABSTRACT: The purpose of this study is to investigate the effect of auditory perceptual phonetic training on the identification and production of English vowels by Cypriot Greek children and adults. Another two groups of Cypriot Greek child and adult speakers served as controls. The trained groups participated in the pretest, training, and posttest phase, while the controls completed only the pretest and posttest phase. The results showed that perceptual training improved identification accuracy, with children showing greater gains than adults. Although the performance of adults was poorer than the performance of children, their phonological system did undergo substantial alteration through perceptual phonetic training as they significantly improved their identifications in the posttest. Also, the results support a common mental space for the speech perception and production domains since the perceptually-oriented training affected the learners' productions. However, transfer of improvements in production was observed only to some extent in children and not in adults, suggesting that training has an impact mostly on the trained modality and that some production improvement after perceptual training might be more evident in younger learners.